Meningkatkan Kompetensi Guru Menyusun Modul Melalui Supervisi Akademik di SMAS Baiturrahmah Padang - Jusmiwarti BJ (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
This study reviews the improvement of Teacher Competence in Composing Teaching Modules through Academic Supervision at SMAS Baiturrahmah Padang. This study aims to increase teacher competence in compiling teaching modules, thereby increasing the effectiveness of achieving mastery of learning objectives by students. The method used in this study is Action Research which consists of 2 (two) cycles, and each cycle consists of Planning, Implementation, Observation, and Reflection. The results showed that (1) in the formulation of the learning objectives indicator component, there was an increase from 61.1% in initial competence to 71.8% in cycle I and in cycle II it increased to 72.5%; (2) In the component of determining learning materials and materials, there was an increase in competence from 52.9% to 67.1% after cycle I and in cycle II it was stronger to 72.9%; (3) In the strategy and learning method selection component, there was a significant increase from the initial 56.4% to 61.2% in cycle I and increased again to 71.8% after cycle II; (4) Even though there was no sharp increase, there was also an increase in the selection of media and learning tools from 50.6% at the beginning of the activity and 58.2% after cycle I to 71.8% after cycle II; (5) We can also see a significant increase in the learning evaluation planning component. From the initial 47.0% at the beginning of the activity, it became 56.5% at the end of cycle I and managed to reach 70.6% at the end of cycle 2. Based on the acquisition of research data in this school action research activity, it was concluded that academic supervision can increase teacher competence in compiling teaching modules at SMAS Baiturrahmah Padang.